ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL OPERASI HITUNG PERKALIAN PADA SISWA KELAS IV - Mardiyah, Niswatul; Pujianto, Hanif; Azmina, Alfina Tahta; Ermawati, Diana (LPPM Universitas Nias Raya, 2025)
This study aims to reveal various obstacles faced by fourth grade students in solving mathematical story problems related to multiplication operations. Learning difficulties are conditions when students are unable to follow the learning process optimally. Story problems require the ability to think logically, understand mathematical language, and apply the concepts learned, so they often become obstacles for students. This study uses a narrative qualitative approach. Data collection techniques include observation, interviews, and documentation. Data analysis was carried out through the Miles and Huberman interactive model, which includes the stages of data collection, reduction, presentation, and drawing conclusions. The results of the data analysis revealed that students faced several difficulties in solving multiplication problems, including: obstacles in understanding the concept of multiplication, not yet mastering multiplication memorization and difficulty solving multiplication problems. The various factors that trigger these difficulties are low motivation and interest in learning, limited variations in learning strategies, less than optimal understanding of mathematics, and lack of mastery of mathematical language.